Prosedur Modifikasi Perilaku Penyisihan Sesaat dalam Mengembangkan Kemampuan Emosional Anak Usia Dini (Studi Kasus Kelompok A di TK Pertiwi Macanan Kebakkramat Tahun 2015/2016) - Wahyuningsih, Chahya, Dra. Surtikanti, S.H.,M.Pd (2016)
This study aims to determine the allowance for instantaneous (time out) behavior modification procedures in developing early childhood emotional abilities group A of TK Pertiwi Macanan Kebakkramat. This problem was investigated using qualitative approach by using case study. The execution time in November 2015 to March 2016. The data were collected through interview, observation, and documentation. The data were analyzed descriptively and qualitatively by using an interactive model. The data results of the study were retested validity using triangulation of data, methods and theories. From the research allowance behavior modification procedures given moment in TK Pertiwi Macanan Kebakkramat particular group A which recall inauguration that had been given in the form of actions and words aimed to warn the children that the negative behavior emerge. Children who didn't perform activities, didn't want to be reminded, scrambling with friends, and behave as he pleased himself, the child got the preliminary procedures shortly. When the moment of allowance behavior modification procedures performed repeatedly to the same child with withdrawal inauguration the same or different, this made the child didn't want to misbehave. Kids naturally understood, in other words the teacher managed to develop emotional abilities and provide habituation positive attitude towards children.